Definitive lobectomy without frozen section analysis is a treatment option for large or deep nodules selected carefully with clinical diagnosis of malignancy. Issue 7 (22nd May 2020) - Mori, Shohei; Noda, Yuki; Shibazaki, Takamasa; Kato, Daiki; Matsudaira, Hideki; Hirano, Jun; Ohtsuka, Takashi
Abstract: Background: Tissue harvesting for patients with a lung nodule is sometimes unsuitable due to the size and location of the nodule. In such cases, it is unclear whether it is acceptable to proceed to definitive lobectomy without intraoperative frozen section analysis. Methods: We retrospectively reviewed patients who underwent definitive lobectomy or wedge resection for frozen section analysis at our institution between 2014 and 2018. The sensitivity, specificity, and accuracies of the clinical and frozen section diagnoses were evaluated against the final pathological diagnosis. Results: There were 141 patients in the definitive lobectomy group and 58 patients in the frozen section analysis group, with the latter having smaller and less deep nodules and a lower rate of malignancy on clinical and final pathological diagnoses. The sensitivity, specificity, and accuracy of the clinical diagnosis were 100%, 82%, and 95%, respectively, in the frozen section analysis group and 99%, 67%, and 97%, respectively, in the definitive lobectomy group; values of frozen section diagnosis were 98%, 82%, and 93%, respectively. On subgroup analysis, all ground‐glass nodules clinically diagnosed as malignant had a final pathological diagnosis of malignancy. Conclusions: The accuracy of the clinical diagnosis was high and was not inferior to the frozen section diagnosis. These data suggest that definitive lobectomy is an acceptable treatment option for carefully selected patients with large or deep nodules and ground‐glass nodules clinically diagnosed as malignant. To avoid unnecessary lobectomy, frozen section diagnosis should be considered for nodules likely to be benign. Key points: Significant findings of the study: The accuracy of the clinical diagnosis was high and was not inferior to the frozen section diagnosis. What this study adds: Definitive lobectomy is an acceptable treatment option for carefully selected patients with large or deep nodules and ground‐glass nodules with a clinical diagnosis of malignancy.